2012
DOI: 10.4103/0972-0707.94588
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between three different pit and fissure sealants with regard to marginal integrity

Abstract: Aim:The aim of this study is to compare the occurrence of enamel fractures, sealant fractures and marginal fissures after placement of three sealants: Helioseal F, Conseal F and Clinpro.Materials and Methods:Thirty individuals between 13 and 15 years of age, diagnosed with pit and fissure caries by visual and DIAGNOdent examination, were chosen for sealant placement on their mandibular molars. The sealants were placed at random, after which, impressions were made with polyvinyl siloxane and casts were fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Occlusal surface accounts for 12.5% of the total tooth areas of teeth. [ 1 ] Fissure caries is most common in children due to deep pit and fissures. [ 2 ] Pit and fissures are classified as self-cleansable (V and U type) and nonself cleansable (I and k type).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Occlusal surface accounts for 12.5% of the total tooth areas of teeth. [ 1 ] Fissure caries is most common in children due to deep pit and fissures. [ 2 ] Pit and fissures are classified as self-cleansable (V and U type) and nonself cleansable (I and k type).…”
Section: Introductionmentioning
confidence: 99%
“…Unfavorable morphology makes these fissures difficult for salivary access and minimizes fluoride deposition for preventive effect. [ 1 2 3 ] Fissure caries accounts for 50% of all the carious lesions. [ 1 ] Pit and fissures areas on the occlusal surface of the teeth make them susceptible to dental caries which need to be prevented or restored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding resin-based sealants, our results revealed that unfilled resin sealer Clinpro showed a high retention rate than filled resin sealant Helioseal F. Other studies also concluded the same results. 10,14,24 Low filler content of Clinpro when compared to Helioseal F resulted in low viscosity. 24 Low viscosity of unfilled resin sealant enables it to penetrate deeper in the narrow and irregular anatomy of the fissures.…”
Section: Discussionmentioning
confidence: 99%
“…Sealants have been the subject of numerous studies evaluating effectiveness, adaptation and penetration into fissures and fluoride release 4,9 . In the oral environment, dental material is also subjected to chemical and physical insults.…”
Section: Introductionmentioning
confidence: 99%